Utilizing Visual Images Of Autism Behavioral Symptoms In Facebook Application For Raising An Awareness Among Secondary School Teachers In Pulau Pinang - Dolah, Jasni; Balraj Baboo, Shanthi; Mat Desa, Mohd Asyiek; Mohd Bakhir, Norfarizah (2016)

(untitled)
This paper highlights the outcomes of utilizing visual images of Autism behavioural symptoms using Facebook application to increase awareness among secondary school teachers in Pulau Pinang. The issues of identifying autism symptoms have always been questions to many of us. Autism always misinterpreted and associated with a group of complex disorders of brain development, these disorders are characterized in varying degrees, by difficulties in social interaction, verbal and nonverbal communication and repetitive behaviours. The conventional method in identifying autism symptoms was limited and too clinical to be understood by the societies. Furthermore, children diagnosed with autism tend to have different behaviour which difficult to recognised. By utilizing social media apps such as Facebook, it helped the teachers to increase their awareness towards basic symptoms of these children’s. Selected images of autism behavioural symptoms were hand drawn and posted to the Facebook application for the identification purposes from the respondents. This research investigated the effects of visual images on Facebook based on how many ‘Like’ or ‘Dislike’ features given by respondents. Based from the outcomes, it’s revealed that the use of visual images in Facebook application managed to increase the awareness towards identifying autism behavioural symptoms